الآثار المالية والنقدية للدين العام الداخلي في العراق للمدة 2004-2020 - الرفاعي، محمد إبراهيم ضاحي; العبيدي، سعيد علي محمد (جامعة الأنبار - كلية الإدارة والاقتصاد, 2022)
يعاني الاقتصاد العراقي من عجز الموازنة العامة في السنوات الأخيرة قيد البحث، يعود ذلك إلى ارتفاع النفقات العامة لاسيما العسكرية منها بغية مواجهة التنظيمات الإرهابية، إذ يتم تمويل عجز الموازنة عن طريق بيع الأوراق المالية الحكومية، مما أدى ذلك إلى ارتفاع حجم الدّين العام الداخلي في العراق، أي أن الزيادة في حجم الدين العام الداخلي تعمل على التأثير في المتغيرات الاقتصادية المالية والنقدية. انطلاقاً من الأهمية الكبيرة التي تحظى بها الآثار المالية والنقدية للدين العام الداخلي يهدف البحث إلى: تحليل تطور حجم وهيكل الدين العام الداخلي في العراق وبيان الآثار المالية والنقدية للدين العام الداخلي في العراق. وتوصل البحث إلى أن تزايد الدين العام الداخلي وخصوصاً منذ عام (2014)، لا يعد بالضرورة مؤشراً سلبياً أو دين عقيم بشكل كامل، في حين ساهمت هذه الديون في الحفاظ ولو جزئياً على الاستقرار الاقتصادي والسياسي والاجتماعي، كما أنها أسهمت في تحرير الأراضي العراقية التي احتلها التنظيمات الإرهابية فضلاً عن إعادة الحقول النفطية إلى الخدمة واستئناف النشاط الاقتصادي في تلك المناطق. إذ أن اللجوء إلى ذلك الدين لا يعكس بالضرورة صورة سلبية عن الاقتصاد بل يتوقف على الكيفية التي يتم بها تخصيص الموارد المالية الناجمة عن الاستدانة. The Iraqi economy suffers from the general budget deficit in the recent years under discussion, due to the rise in public expenditures, especially military ones, in order to confront terrorist organizations, as the budget deficit is financed by selling government securities, which led to a rise in the volume of the internal public debt in Iraq. That is, the increase in the volume of the internal public debt is working to influence the financial and monetary economic variables. Proceeding from the great importance of the financial and monetary effects of the internal public debt, the research aims to: Analyze the evolution of the volume and structure of the internal public debt in Iraq and to show the financial and monetary effects of the internal public debt in Iraq. The research concluded that the increase in the internal public debt, especially since (2014), is not necessarily a negative indicator or a completely sterile debt, while this debt contributed, even partially, to economic, political and social stability, and also contributed to the liberation of the Iraqi lands it occupied. terrorist organizations, as well as restoring oil fields to service and resuming economic activity in those areas. As resorting to that debt does not necessarily reflect a negative image of the economy, but rather depends on how the financial resources resulting from debt are allocated.
Keywords: السياسات المالية -- الاقتصاد العراقي -- الموازنة العامة -- الديون الداخلية